Continuous or interval aerobic exercise training reduces daily fructose intake in female Wistar rat - Oharomari, Leandro Kansuke [UNESP]; Manfredi, Mateus Luís; Joaquim, Anderson Gregório; Chimin, Patricia; De Moraes, Camila (FapUNIFESP (SciELO), 2022)
Objctive Fructose consumption has increased worldwide. Excessive fructose intake has been a risk factor for the increased metabolic syndrome disorder incidence. This study aimed to investigate the possible influence of two different exercise training methods, continuous and interval, on fructose intake. Methods Thirty two-months-old female Wistar rats were divided into six groups: sedentary + water; sedentary + fructose; continuous training + water; interval training + water; continuous training + fructose; interval training + fructose. Fructose was given in drinking water (10%). Continuous (40 minutes at 40% maximal speed) or interval training (28 minutes, 1 minute at 70%; 3 minutes at 35% maximal speed) sessions were carried out 3 days/week for 8 weeks. Results Fructose consumption decreased food intake with a concomitant increase in fluid intake. Continuous and interval training did not modify food intake but progressively reduced fructose ingestion. In the 8th week, interval training + fructose and continuous training + fructose groups drank less fructose solution, 35% and 23%, respectively, than sedentary + fructose group.Conclusion The findings indicate that both continuous and interval aerobic exercise training seem to modulate food behavior, possibly by mitigating the craving for sweetness, with interval training being more effective in reducing fructose intake than continuous exercise
Exercício físico aeróbio contínuo ou intervalado reduz ingestão de frutose em ratas Wistar
Keywords: Appetite; Exercise; Female; Fructose